Implementation Of A Deep Learning-Based Approach In Islamic Religious Education At Madrasah Tsanawiyah Muallimin In Medan - Siregar, Rahmayani; Siregar, Nur Aisyah; Siregar, Nurkholijah; Nasution, Saidatun Nisa (Journal of English Language and Education, 2026)
This study employs a qualitative approach with a descriptive research design to examine the implementation of the Deep Learning approach in Islamic Religious Education at Muallimin Islamic Junior High School (MTs) Medan under the Kurikulum Merdeka framework. The research subjects were selected through purposive sampling, involving the school principal, the vice-principal of curriculum affairs, Islamic Religious Education teachers, and students who demonstrated a comprehensive understanding of the learning process. Data were collected through in-depth interviews, field observations, and documentation. The results indicate that: first, lesson planning for Deep Learning-based Islamic Religious Education involves the preparation of teaching modules that include triggering questions, clear learning objectives, and structured time allocations; second, the classroom implementation effectively integrates the three pillars of Deep Learning, namely Mindful Learning (connecting), Joyful Learning (experiencing), and Meaningful Learning (creating meaning); third, the post-implementation evaluation reveals that the Deep Learning approach contributes positively to the overall effectiveness of Islamic Religious Education at MTs Muallimin Medan.